Dg93, a Nodule-Abundant mRNA of Datisca glomerata with Homology to a Soybean Early Nodulin Gene - Okubara, Patricia A. (American Society of Plant Physiologists, 2000)
We have isolated a 590-bp full-length cDNA clone designated Dg93, an mRNA that is highly expressed in symbiotic root nodules of the actinorhizal host Datisca glomerata. Dg93 mRNA encodes a deduced polypeptide of 105 amino acids with significant identity (74%) to the soybean (Glycine max) early nodulin (ENOD) gene GmENOD93 (Kouchi and Hata, 1993). Dg93 mRNA is abundant in nodules at 4 weeks post inoculation, the earliest time assayed, and steady-state mRNA levels remain elevated 11 weeks after inoculation. Spatial patterns of Dg93 mRNA expression are complex, with transcript accumulation in the nodule lobe meristem, early infection zone, periderm, and cells of the vascular cylinder, but not in the surrounding uninfected cortical cells. Dg93 is encoded by a small gene family in D. glomerata. To our knowledge, this is the first report of a gene from an actinorhizal host that is expressed in the nodule meristem and that shares sequence homology with an early nodulin gene from a legume.